Electrode
By using conductive polymers and ionized polymer components in lithium-ion battery electrodes, combined with appropriate amounts of active substances and adhesives, the problems of high cost of conductive materials and insufficient capacity retention are solved, and cost-effective battery performance improvement is achieved.
Patent Information
- Application Number
- CN202480008435.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-06
- Filing Date
- 2024-02-05
- Publication Date
- 2025-08-22
AI Technical Summary
Among the existing lithium-ion battery electrode materials, the conductive material with excellent conductivity is costly, resulting in uneconomical production, degradation of battery performance, and insufficient capacity retention.
An electrode structure containing conductive polymer and ionized polymer components is adopted, and an electrode with excellent conductivity is formed by controlling the solubility parameters and molecular weight ratio of the resin, combined with an appropriate amount of active substance and binder.
While achieving economical production, the conductivity and capacity retention rate of the battery electrode are improved, ensuring the stability and efficient use of battery performance.
Smart Images

Figure CN120530503A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode, in particular to an electrode and applications of the electrode. Background Art
[0002] In recent years, demand for mobile devices such as smartphones, tablets (PCs), and wireless headphones has been increasing. Furthermore, with the advancement of electric vehicles, energy storage batteries, robots, satellites, and other applications, research is actively underway on high-performance secondary batteries that can be repeatedly charged and discharged as energy sources.
[0003] Currently commercialized secondary batteries include nickel-cadmium batteries, nickel-metal hydride batteries, nickel-zinc batteries, and lithium secondary batteries. Compared to nickel-based secondary batteries, lithium secondary batteries have almost no memory effect, allowing them to be charged and discharged freely, with a very low self-discharge rate and high energy density.
[0004] The term "electrode" refers to a positive electrode and a negative electrode of a battery cell. The electrode is generally manufactured by applying a slurry containing an electrode active material onto a current collector in the form of a metal plate and then drying the slurry.
[0005] The slurry may contain a conductive material to improve electrical conductivity. To ensure excellent electrical conductivity, a large number of methods use conductive materials with excellent electrical conductivity. However, conductive materials with excellent electrical conductivity are generally expensive, and their large-scale use has industrial disadvantages.
[0006] When the content of conductive materials is reduced, although economical production can be achieved, the performance of the battery cell may not be able to be exerted normally due to the reduction in conductivity.
[0007] Therefore, a technology that can build an economical production system and fully utilize the performance of battery cells is needed.
[0008] [Prior art literature]
[0009] [Patent Document]
[0010] (Patent Document 1) Korean Patent Publication No. 10-2022-0150693 (Invention Title: High-Voltage Battery Module with Excellent Cooling Efficiency)
[0011] (Patent Document 2) Korean Patent Publication No. 10-2022-0142853 (Invention Title: Battery Pack and Manufacturing Method Thereof)
[0012] [Non-patent literature]
[0013] (Non-Patent Document 1) Handbook of Solubility Parameters and Other Cohesion Parameters, 2nd edition. CRC Press
[0014] (Non-patent document 2) J. Brandrup, EH Immergut, and EA Grulke, des. Polymer Handbook, 4th ed., Wiley-Interscience, New York, 1999.
[0015] (Non-patent document 3) Yanlong Luo et al., 2017, J. Phys. Chem. C 2017, 121, 10163-10173 Summary of the Invention
[0016] (1) Technical issues to be resolved
[0017] An object of the present invention is to provide an electrode having excellent electrical conductivity.
[0018] Another object of the present invention is to provide an electrode having an excellent capacity retention rate.
[0019] Furthermore, an object of the present invention is to provide a battery cell, a battery module, and a battery pack including the electrode, and to provide an electric device including at least one of the battery cell, the battery module, and the battery pack.
[0020] (2) Technical solution
[0021] An electrode according to an example of the present invention may include a current collector and an active material layer located on at least one side of the current collector, wherein the active material layer may include an active material, a binder, and a conductive polymer, the conductive polymer may include a conductive component and an ionized polymer component, and the binder may include SP according to the following formula 1 d 30 (MPa) 1 / 2 The following resin A, the polymer component may include SP according to the following formula 1 d 30 (MPa) 1 / 2 The following resin B.
[0022] 20
[0023] [Formula 1]
[0024] SP d=SP W -SP P
[0025] In formula 1, SP W is the solubility parameter of water measured at 25°C, SP P is the solubility parameter of the resin A or the resin B measured at 25°C.
[0026] In the electrode according to one example of the present invention, the solubility parameter (SP) of the resin A measured at 25°C is P1 ) and resin B measured at 25 ° C solubility parameter (SP P2 ) ratio (SP P1 / SP P2 ) can be in the range of 0.8 to 1.2.
[0027] In the electrode according to one embodiment of the present invention, the weight average molecular weight (M W1 ) and the weight average molecular weight of resin B (M W2 ) ratio (M W1 / M W2 ) can be in the range of 0.1 to 20.
[0028] In the electrode according to one embodiment of the present invention, the weight average molecular weight (M W2 ) can be in the range of 2000 g / mol to 200000 g / mol.
[0029] In the electrode according to one example of the present invention, the resin A and the resin B may each independently have a glass transition temperature (Tg) of 50° C. or higher.
[0030] In an electrode according to an example of the present invention, the conductivity of the conductive polymer measured by a four-point probe method at 25°C may be 2×10 -3 S / cm or more.
[0031] In the electrode according to one example of the present invention, the conductive component and the ionized polymer component in the conductive polymer may be electrically combined.
[0032] In the electrode according to one example of the present invention, the conductive polymer may include 10 wt % or more of the ionized polymer component relative to the total weight of the conductive polymer.
[0033] In the electrode according to one example of the present invention, the conductive polymer may include a conductive component in a range of 30 parts by weight to 800 parts by weight relative to 100 parts by weight of the ionized polymer component.
[0034] In the electrode according to one embodiment of the present invention, the weight of the binder (W B ) and the weight of the conductive polymer (W CP ) ratio (W B / W CP ) can be in the range of 1 to 100.
[0035] In the electrode according to one example of the present invention, the content of the conductive polymer may be 1 wt % or less relative to the total weight of the active material layer.
[0036] In the electrode according to one example of the present invention, the content of the active material may be in the range of 80 wt % to 99 wt % with respect to the total weight of the active material layer.
[0037] In the electrode according to one example of the present invention, the active material may include a carbon active material and a silicon active material.
[0038] In an electrode according to one example of the present invention, the active material may contain a carbon active material in a range of 80 weight % to 99 weight % relative to the total weight of the active material, and the active material may contain a silicon active material in a range of 0.01 weight part to 30 weight parts relative to 100 weight parts of the carbon active material.
[0039] In an electrode according to one embodiment of the present invention, the average particle size (D C ) and the average particle size of the silicon active material (D Si ) ratio (D C / D Si ) can be in the range of 0.1 to 10.
[0040] In the electrode according to one example of the present invention, the active material layer may further include a conductive material, and the content of the conductive material may be 0.2 wt % or less relative to the total weight of the active material layer.
[0041] A battery cell according to an example of the present invention may include a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, wherein the negative electrode may be an electrode according to an example of the present invention. In the following formula 2, when n is 100, L R It can be more than 80%. When n is 200, L R It can be 55% or more.
[0042] [Formula 2]
[0043] L R =L2 / L1×100(%)
[0044] In Equation 2, L1 is the discharge capacity of the first cycle at 25°C, and L2 is the discharge capacity of the nth cycle at 25°C. One cycle is defined as charging to 4.2 V at 0.5C using CC-CV charging mode, then discharging to 2.7 V at 0.05C and 0.5C at 25°C.
[0045] A battery module according to an example of the present invention may include one or more battery cells, wherein the battery cells may be battery cells according to an example of the present invention.
[0046] A battery pack according to an example of the present invention may include one or more battery cells or one or more battery modules, wherein the battery cells may be battery cells according to an example of the present invention, and the battery modules may be battery modules according to an example of the present invention.
[0047] An electrical device according to an example of the present invention may include one or more selected from one or more battery cells, one or more battery modules and one or more battery packs, wherein the battery cell may be a battery cell according to an example of the present invention, the battery module may be a battery module according to an example of the present invention, and the battery pack may be a battery pack according to an example of the present invention.
[0048] (3) Beneficial effects
[0049] The present invention can provide an electrode having excellent electrical conductivity.
[0050] Furthermore, the present invention can provide an electrode having excellent capacity retention.
[0051] Furthermore, the present invention may provide a battery cell, a battery module, and a battery pack including the electrode, and may provide an electric device including at least one of the battery cell, the battery module, and the battery pack. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 is a schematic diagram showing an exemplary structure of a battery cell according to one example of the present invention.
[0053] Figure 2 is a schematic diagram illustrating an exemplary structure of a battery module according to one example of the present invention.
[0054] Figure 3 is a schematic diagram showing an exemplary structure of a battery pack according to one example of the present invention. Best Practice
[0055] The description of the embodiments disclosed in the present invention is merely illustrative for the purpose of illustrating the embodiments according to the technical concept of the present invention. In addition, in addition to the embodiments disclosed in the present invention, the embodiments according to the technical concept of the present invention can be implemented in various forms. In addition, the technical concept of the present invention should not be interpreted as being limited to the embodiments described in the present invention.
[0056] Among the physical properties mentioned in the present invention, if the measurement temperature has an impact on the physical properties, unless otherwise specified, the physical properties are physical properties measured at normal temperature and pressure.
[0057] The term normal temperature used in the present invention may refer to a natural temperature that is not heated or cooled, for example, any temperature within the range of 10° C. to 30° C., for example, a temperature of about 15° C. or higher, about 18° C. or higher, about 20° C. or higher, about 23° C. or higher, about 27° C. or lower, or 25° C. In the present invention, unless otherwise specified, the unit of temperature is degrees Celsius (° C.).
[0058] Among the physical properties mentioned in the present invention, when the measurement pressure has an effect on the physical properties, unless otherwise specified, the physical properties are physical properties measured under normal pressure.
[0059] The term normal pressure used in the present invention refers to natural pressure without being pressurized or reduced, and generally, the gas pressure within the range of about 700 mmHg to 800 mmHg is referred to as normal pressure.
[0060] The term a to b as used herein means including a and b and being within a range between a and b. For example, comprising a to b parts by weight is the same as being within a range comprising a to b parts by weight.
[0061] The present invention can provide an electrode with excellent electrical conductivity. In addition, the present invention can provide an electrode with excellent capacity retention. In addition, the present invention can provide a battery cell 1, a battery module 2, and a battery pack 3 including the electrode, and can provide an electrical device including at least one of the battery cell 1, battery module 2, and battery pack 3. Examples of the battery cell 1, battery module 2, and battery pack 3 can be referred to respectively. Figures 1 to 3 .
[0062] An electrode according to an embodiment of the present invention may include a current collector and an active material layer. The active material layer may be located on at least one side of the current collector.
[0063] In the electrode according to one example of the present invention, a material having electrical conductivity and electrochemical durability may be used as the current collector.
[0064] In addition, the material of the current collector can be determined according to whether the electrode is a positive electrode or a negative electrode. When the electrode is a positive electrode, the current collector can be a positive electrode current collector, and when the electrode is a negative electrode, the current collector can be a negative electrode current collector. In addition, as long as the positive electrode current collector does not cause chemical changes in the battery cell 1 and has conductivity, its type, size and shape are not particularly limited. The positive electrode current collector can use, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or a material whose surface is treated with carbon, nickel, titanium or silver. As long as the negative electrode current collector does not cause chemical changes in the battery cell 1 and has conductivity, its type, size and shape are not particularly limited. The negative electrode current collector can use, for example, copper, stainless steel, nickel, titanium, calcined carbon, a material whose surface is treated with carbon, nickel, titanium, silver, or a copper-cadmium alloy.
[0065] In addition, the current collector may have an appropriate thickness as needed. Although not particularly limited, the current collector may have a thickness in the range of 1 μm to 500 μm, or may have a thickness in the range of 1 μm to 300 μm, or may have a thickness in the range of 1 μm to 100 μm, or may have a thickness in the range of 1 μm to 50 μm.
[0066] Unless otherwise specified, the terms thickness (or height), width and length used in the present invention represent average values and can be measured by measuring devices that can measure thickness (or height), width and length respectively and according to methods in the present technical field.
[0067] In addition, the current collector may have fine concavoconvexities on its surface to further enhance the adhesion to the active material layer. For example, the current collector may be in the form of one or more selected from a film, sheet, foil, mesh, porous body, foam, and non-woven fabric.
[0068] In an electrode according to an embodiment of the present invention, an active material layer may be formed from a slurry composition. Specifically, the active material layer may be a dried form of the slurry composition, and as needed, the active material layer may be a form in which the slurry composition is dried and then rolled.
[0069] As used herein, the term "dry" refers to a state in which substantially no solvent is present, and for example, refers to a state in which the amount of solvent contained in each layer is approximately 1% by weight or less, 0.5% by weight or less, 0.1% by weight or less, or 0.05% by weight or less. The drying conditions employed for this purpose are not particularly limited and can be adjusted to achieve the aforementioned amount of solvent.
[0070] In addition, the active material layer can be formed by applying the slurry composition on at least one side of the current collector and drying. As described above, as needed, calendering can be performed after drying. The calendering method can be performed by a calendering fixture or the like according to a known method. In addition, the coating method is not particularly limited, and a known method can be used. Specifically, the coating method can use a blade coating method, a dip coating method, a reverse roller coating method, a forward roller coating method, a gravure coating method, an extrusion method or a brush coating method, etc. Taking into account the thickness after drying, the coating thickness of the slurry composition can be applied with an appropriate thickness, and according to the coating thickness, the above-mentioned known method can be appropriately selected for implementation.
[0071] In addition, the slurry composition can be coated on at least one side of the current collector at an appropriate loading amount suitable for the purpose. The loading amount is not particularly limited, but for example, it can be 1 mg / cm 2 Above, 2mg / cm 2 Above, 3mg / cm 2 Above, 4mg / cm 2 Above, 5mg / cm 2 Above, 6mg / cm 2 Above, 7mg / cm 2 Above or 8mg / cm 2 Above, or can be 50mg / cm 2 Below, 45mg / cm 2 Below, 40mg / cm 2 Below, 35mg / cm 2 Below, 30mg / cm 2 Below, 25mg / cm 2 Below, 20mg / cm 2 Below or 10mg / cm 2 Below, or within a range formed by appropriately selecting the above upper and lower limits.
[0072] In addition, the slurry composition coated on at least one side of the current collector can be dried at an appropriate temperature and time. The drying can be performed in an oven, and the temperature of the oven can be set to 50° C. or higher, 60° C. or higher, 70° C. or higher, 80° C. or higher, 90° C. or higher, or 100° C. or higher for drying. In addition, the drying time can be performed within an appropriate range taking into account the drying temperature.
[0073] The slurry composition forming the active material layer may include various components. In addition, the slurry composition may be in a state in which the various components are appropriately dispersed. The slurry composition can be prepared by adding the various components according to an appropriate method and order using an appropriate mixing method. The mixing method is not particularly limited, and a known method can be used. Specifically, the mixing method can use a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, an ultrasonic disperser, a homogenizer, a planetary mixer or a Filmix mixer. The specific content of the slurry composition forming the active material layer is described below.
[0074] The active material layer may be in direct contact with the current collector, and even if the active material layer is not in direct contact with the current collector, it may be located on the current collector. For example, a separate layer may be provided between the current collector and the active material layer.
[0075] In an electrode according to an example of the present invention, the active material layer may be a single layer. In another example, the active material layer of the electrode may be a multilayer layer.
[0076] In an electrode according to an example of the present invention, the active material layer may include an active material. The active material layer may include more than 80% by weight, more than 81% by weight, more than 82% by weight, more than 83% by weight, more than 84% by weight, more than 85% by weight, more than 86% by weight, more than 87% by weight, more than 88% by weight, more than 89% by weight, more than 90% by weight, more than 91% by weight, more than 92% by weight, more than 93% by weight, more than 94% by weight or more than 95% by weight, or less than 99% by weight, less than 98.5% by weight or less than 98% by weight of the active material relative to the total weight of the active material layer. In addition, the active material layer may include an active material within the range formed by appropriately selecting the above upper and lower limits. By making the active material layer of the electrode include an active material within the above range, excellent capacity retention can be achieved.
[0077] In an electrode according to one embodiment of the present invention, the active material of the active material layer may vary depending on whether the electrode is a positive electrode or a negative electrode. When the electrode is a positive electrode, the active material may be a positive electrode active material. Alternatively, when the electrode is a negative electrode, the active material may be a negative electrode active material.
[0078] The positive electrode active material is not particularly limited, but for example, can be exemplified by: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or compounds substituted with one or more transition metals; lithium iron oxides such as LiFe3O4; 1+c1 Mn 2-c1Lithium manganese oxides such as LiMnO4 (0≤c1≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 or Cu2V2O7; 1-c2 M c2 Ni-site lithium nickel oxide represented by O2 (wherein M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); 2-c3 M c3 Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from Fe, Co, Ni, Cu and Zn); lithium nickel cobalt manganese (NCM) composite oxides, lithium nickel cobalt manganese aluminum (NCMA) composite oxides and LiMn2O4 in which part of the Li in the chemical formula is substituted by alkaline earth metal ions, etc.
[0079] The negative electrode active material is not particularly limited, but for example, a compound that can reversibly intercalate and deintercalate lithium can be used. Specific examples include: carbon-based materials such as graphite (artificial graphite, natural graphite, or graphitized carbon fiber) or amorphous carbon; metal-based compounds that can alloy with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; SiO β(0 < β ≤ 2), metal oxides that can be doped (dope) and dedoped with lithium, such as SnO2, vanadium oxide, lithium vanadium oxide; or composites containing the metal-based compounds and carbon-based materials, such as Si-C composites or Sn-C composites, and any one of them or a mixture of two or more of them can be used. In addition, as the negative electrode active material, a metallic lithium thin film can be used. As the carbon material, low-crystalline carbon and high-crystalline carbon can be used. Representative examples of low-crystalline carbon include soft carbon and hard carbon. Examples of highly crystalline carbon include amorphous, flaky, spherical, or fibrous natural graphite or artificial graphite, primary graphite (Kish graphite), pyrolytic carbon, mesophase pitch-based carbon fiber, carbon microbeads (mesocarbon microbeads), mesophase pitch, and high-temperature calcined carbon such as petroleum and coal-based coke (petroleum or coal tar pitch-derived coke).
[0080] In an electrode according to an embodiment of the present invention, the active material of the active material layer may include a carbon active material and a silicon active material. The carbon active material and the silicon active material may be materials capable of transporting electrons in a lithium battery cell, for example.
[0081] The carbon active material is not particularly limited, and any carbon active material commonly used in the art can be used. Examples of the carbon active material include amorphous carbon, graphite, natural graphite, artificial graphite, mesocarbon microbeads, and pitch-based carbon fibers. These carbon active materials can be used alone or in combination.
[0082] The silicon active material may include silicon (Si), alloys containing silicon, SiO, SiO2, SiO x , Si-containing materials coated with conductive carbon, or composites of Si-containing materials and conductive carbon. These silicon active materials can be used alone or in combination. Using silicon active materials can achieve higher capacity.
[0083] Examples of the silicon-containing alloy include alloy compositions containing silicon and at least one element selected from titanium, iron, cobalt, nickel, and copper. Furthermore, examples of the silicon-containing alloy include alloy compositions containing silicon, transition metals such as aluminum and iron, or containing silicon, tin, and rare earth elements such as yttrium.
[0084] SiO x It may be a compound containing at least one of SiO and SiO2 and Si, wherein x is usually in the range of 0.01 or more and less than 2. SiO x For example, SiO can be formed by a disproportionation reaction. Specifically, SiO x It can be prepared by heat-treating SiO2 in the presence of a polymer such as polyvinyl alcohol to generate silicon and silicon dioxide. The heat treatment can be performed after the SiO2 and the polymer are pulverized and mixed in an atmosphere containing organic gas and / or steam, for example, at a temperature of about 900°C or above or about 1000°C or above.
[0085] Composites of Si-containing materials and conductive carbon include, for example, compounds formed by heat-treating a pulverized mixture of SiO and a polymer such as polyvinyl alcohol and any carbon material in an atmosphere containing organic gas and / or steam. Furthermore, the composite can also be obtained by known methods, for example, by coating the surface of SiO particles by a chemical deposition method using an organic gas or the like, or by forming composite particles (granulation) of SiO particles and graphite or artificial graphite by a mechanochemical method.
[0086] In an electrode according to an example of the present invention, the active material of the active material layer may include 80% by weight or more, 81% by weight or more, 82% by weight or more, 83% by weight or more, 84% by weight or more, 85% by weight or more, 86% by weight or more, 87% by weight or more, 88% by weight or more, 89% by weight or more, or 99% by weight or less, 98% by weight or less, 97% by weight or less, 96% by weight or less, 95% by weight or less, 94% by weight or less, 93% by weight or less, 92% by weight or less, or 91% by weight or less of a carbon active material relative to the total weight of the active material. In addition, the active material may include a carbon active material within a range formed by appropriately selecting the above upper and lower limits. By making the active material include a carbon active material within the above range, an excellent capacity retention rate can be achieved.
[0087] In an electrode according to one example of the present invention, the active material of the active material layer may contain more than 0.01 parts by weight, more than 0.05 parts by weight, more than 0.1 parts by weight, more than 0.5 parts by weight, more than 1 part by weight, more than 2 parts by weight, more than 3 parts by weight, more than 4 parts by weight, more than 5 parts by weight, more than 6 parts by weight, more than 7 parts by weight, more than 8 parts by weight, more than 9 parts by weight, more than 10 parts by weight or more than 11 parts by weight, or less than 30 parts by weight, less than 29 parts by weight, less than 28 parts by weight, less than 27 parts by weight, less than 26 parts by weight, less than 25 parts by weight, less than 24 parts by weight, less than 23 parts by weight, less than 22 parts by weight, less than 21 parts by weight, less than 20 parts by weight, less than 19 parts by weight, less than 18 parts by weight, less than 17 parts by weight, less than 16 parts by weight, less than 15 parts by weight, less than 14 parts by weight, less than 13 parts by weight or less than 12 parts by weight of a silicon active material relative to 100 parts by weight of the carbon active material. Furthermore, the active material may include a silicon active material within a range determined by appropriately selecting the upper and lower limits. By controlling the carbon active material and silicon active material content ratio within the above-mentioned range, wrinkling and swelling of the electrode can be prevented, and excellent capacity retention can be achieved.
[0088] In an electrode according to an embodiment of the present invention, the active material may include an average particle size (D C ) is 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, 10 μm or more, 11 μm or more, or 12 μm or more, or 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, or 15 μm or less. In addition, the active material may include an average particle size (D C ) A carbon active material within the range formed by appropriately selecting the upper and lower limits above. By making the active material contain an average particle size (D C ) of the carbon active material, and can have an excellent capacity retention rate.
[0089] In addition, the term average particle size used in the present invention refers to the D50 particle size of the measured object, which can be measured using a Malvern MASTERSIZER 3000 device according to ISO 13320. Specific average particle size measurement can be found in the following <Measurement Methods of Physical Properties>.
[0090] In an electrode according to an embodiment of the present invention, the active material may include an average particle size (D Si) is 0.1 μm or more, 0.5 μm or more, 1 μm or more, 1.5 μm or more, 2 μm or more, 2.5 μm or more, 3 μm or more, 3.5 μm or more, 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, or 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. In addition, the active material may include an average particle size (D Si ) A silicon active material within a range formed by appropriately selecting the upper and lower limits above. By making the active material contain a silicon active material having an average particle size (D Si ) of silicon active material, which can prevent the electrode from wrinkling and swelling, and can have excellent capacity retention.
[0091] In an electrode according to an embodiment of the present invention, the active material may include a carbon active material and a silicon active material in a ratio satisfying an appropriate average particle size. C ) and the average particle size of the silicon active material (D Si ) ratio (D C / D Si ) can be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, 1 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, or 2 or more. In another example, the ratio (D C / D Si ) can be 10 or less, 9.5 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, or 2.5 or less. In another example, the ratio (D C / D Si ) can be within the range formed by appropriately selecting the upper and lower limits. In addition, by making the active material satisfy the ratio (D C / D Si ), which can prevent the electrode from wrinkling and swelling, and can have excellent capacity retention.
[0092] In addition, in the active material, the average particle size (D C ) can be larger than the average particle size of the silicon active material (DSi ). That is, the ratio (D C / D Si ) may be preferably greater than 1. By controlling the average particle size (D C ) is larger than the average particle size of the silicon active material (D Si ), which can prevent the electrode from wrinkling and swelling, and can have excellent capacity retention.
[0093] In addition, in an electrode according to an embodiment of the present invention, the active material may further include a metal active material as needed. As an example, the metal active material may include lithium metal or an alloy containing lithium. Examples of the alloy containing lithium include, but are not limited to, an alloy composition containing lithium and at least one element selected from Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, and Ti.
[0094] In the electrode according to one example of the present invention, the active material layer may include a binder. In the electrode according to one example of the present invention, the active material layer may include a conductive polymer.
[0095] There is no particular limitation on the specific type of the binder, as long as the binder can improve the adhesion between active materials in the active material layer and the adhesion between the active material layer and the current collector.
[0096] In an electrode according to an example of the present invention, the active material layer may contain more than 0.1% by weight, more than 0.5% by weight, more than 1% by weight, more than 1.5% by weight, or more than 2% by weight, or less than 10% by weight, less than 9% by weight, less than 8% by weight, less than 7% by weight, less than 6% by weight, less than 5% by weight, less than 4% by weight, less than 3% by weight, or less than 2.5% by weight of a binder relative to the total weight of the active material layer. In another example, the active material layer may contain a binder within the range formed when the above upper and lower limits are appropriately selected. In addition, by including the binder in an amount within the above range, the adhesion between the active materials in the active material layer and the adhesion between the active material layer and the current collector can be improved, thereby ensuring a characteristic of excellent capacity retention.
[0097] In an electrode according to an example of the present invention, the type of binder of the active material layer is not particularly limited. For example, the binder can be selected from polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), styrene butadiene rubber (SBR), polyethylene oxide (polyethylene oxide), carboxylmethyl cellulose (CMC), cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose (cyanoethyl cellulose), ... At least one of polyols selected from the group consisting of polysucrose, pullulan, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer (poly(ethylene-co-vinyl acetate) copolymer) and polyarylate.
[0098] In an electrode according to an embodiment of the present invention, in order to have excellent conductivity and excellent capacity retention, it is more appropriate to use a conductive material rather than an electrically insulating material as the binder of the active material layer. The binder can be combined with a conductive polymer to achieve the purpose of the present invention.
[0099] In an electrode according to one embodiment of the present invention, the binder of the active material layer is preferably a Lewis acid to ensure excellent conductivity and excellent capacity retention. Specifically, the binder may be an acid in aqueous solution, and the pH measured at 25°C may be less than 7, specifically, the pH may be in the range of 1 to 6.5 or 2 to 6. The pH can be measured according to a known method.
[0100] In the electrode according to one example of the present invention, considering the above-mentioned features and the combination of the conductive polymer described below, the binder of the active material layer may be, for example, polyvinyl alcohol (PVA) or polyacrylic acid (PAA).
[0101] The details of the binder will be described below together with the conductive polymer.
[0102] In an electrode according to one embodiment of the present invention, a conductive polymer may include a conductive component and an ionized polymer component. The ionized polymer component may serve as a template for the conductive polymer. The conductive component and the ionized polymer component in the conductive polymer may be electrically bonded. That is, the conductive component may form a conductive polymer by electrically bonding with the ionized polymer component serving as a template. The electrical bonding may refer to bonding formed by the attractive force generated by dipole-dipole momentum.
[0103] In an electrode according to an example of the present invention, the active material layer may include a conductive polymer of less than 1 wt %, less than 0.9 wt %, less than 0.8 wt %, less than 0.7 wt %, less than 0.6 wt %, less than 0.5 wt %, less than 0.4 wt %, less than 0.3 wt %, less than 0.2 wt % or less than 0.1 wt % relative to the total weight of the active material layer. The lower limit of the content of the conductive polymer is not particularly limited, but in order to ensure appropriate conductivity, for example, the active material layer may include more than 0.01 wt %, more than 0.02 wt %, more than 0.03 wt %, more than 0.04 wt %, more than 0.05 wt %, more than 0.06 wt %, more than 0.07 wt %, more than 0.08 wt % or more than 0.09 wt % of the total weight of the active material layer. In addition, by including the conductive polymer in the above-mentioned range, excellent conductivity can be obtained, and the content ratio of the active material can be increased, thereby having more excellent capacity characteristics.
[0104] The conductive component may be a polymer comprising a specific repeating unit. As long as the conductive component is a homopolymer having conductivity, there is no particular limitation. For example, the conductive component may include one or more selected from nitrogen-containing conductive components and sulfur-containing conductive components, the nitrogen-containing conductive component being, for example, polypyrrole (PPY) or polyaniline (PANI), and the sulfur-containing conductive component being, for example, polythiophene (PT), poly(3,4-ethylenedioxythiophene) (PEDOT) or poly(p-phenylene sulfide) (PPS).
[0105] In an electrode according to an example of the present invention, the conductive polymer may contain an ionized polymer component of 10% by weight or more, 12.5% by weight or more, 15% by weight or more, 17.5% by weight or more, 20% by weight or more, 22.5% by weight or more, or 25% by weight or more relative to the total weight of the conductive polymer. The upper limit of the content of the ionized polymer component is not particularly limited, but for example, the conductive polymer may contain an ionized polymer component of 95% by weight or less, 94% by weight or less, 93% by weight or less, 92% by weight or less, 91% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, 75% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, 55% by weight or less, or 50% by weight or less relative to the total weight of the conductive polymer. In addition, the conductive polymer may contain an ionized polymer component within the range formed when the above upper and lower limits are appropriately selected. In addition, by causing the conductive polymer to contain an ionized polymer component with a content within the above range, it is possible to ensure characteristics of excellent conductivity and excellent capacity retention.
[0106] In an electrode according to an example of the present invention, the conductive polymer may contain 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 100 parts by weight or less, or 800 parts by weight or less, 750 parts by weight or less, 700 parts by weight or less, 650 parts by weight or less, 600 parts by weight or less, 550 parts by weight or less, 500 parts by weight or less, 450 parts by weight or less, or 400 parts by weight or less of a conductive component relative to 100 parts by weight of the ionized polymer component. In addition, the conductive polymer may contain a conductive component within a range formed by appropriately selecting the above upper and lower limits. In addition, by combining the ionized polymer component and the conductive component in the conductive polymer with a content within the above range, it is possible to ensure characteristics of excellent conductivity and excellent capacity retention.
[0107] In an electrode according to one embodiment of the present invention, the ionized polymer component of the conductive polymer may be present in a negatively charged form. In addition, the conductive component of the conductive polymer may be present in a positively charged form. The ionized polymer component and the conductive component may be electrically bonded.
[0108] In an electrode according to one embodiment of the present invention, a specific description is given of an example in which the conductive polymer is PEDOT:PAA. However, PEDOT:PAA is merely an example of a conductive polymer according to one embodiment of the present invention, and it is apparent that the same effects can be achieved even when other conductive components or polymer components are used.
[0109] According to an example of the present invention, the conductive polymer PEDOT:PAA can be prepared by mixing 3,4-ethylenedioxythiophene (EDOT) and polyacrylic acid (PAA) as monomers with an oxidant in water. The oxidant can be ammonium persulfate or ferric persulfate. The EDOT mixture mixed in water is stirred at a certain temperature to synthesize PEDOT, and PEDOT:PAA is synthesized through the electrical connection relationship between PEDOT and ionized PAA based on dipole momentum. As the PEDOT:PAA is synthesized, the reaction solution gradually turns blue (dark blue). Afterwards, the reaction solution can be removed from impurities with a dialysis bag and placed in an ion exchange resin for purification to prepare the final PEDOT:PAA.
[0110] The structure of the PEDOT:PAA prepared as described above may be shown in the following structural formula A. In the structural formula A, m and n may be determined according to the content ratio of EDOT and PAA and the weight average molecular weight of PEDOT:PAA.
[0111] [Structural Formula A]
[0112]
[0113] In the synthesis process of the conductive polymer PEDOT:PAA according to one example of the present invention, the content of the polymer component PAA may be 10 wt % or more, 12.5 wt % or more, 15 wt % or more, 17.5 wt % or more, 20 wt % or more, 22.5 wt % or more, or 95 wt % or less, 94 wt % or less, 93 wt % or less, 92 wt % or less, 91 wt % or less, 90 wt % or less, 85 wt % or less, 80 wt % or less, 75 wt % or less, 70 wt % or less, 65 wt % or less, 60 wt % or less, 55 wt % or less, or 50 wt % or less, relative to the total weight excluding water as a solvent. In addition, the content of the conductive component EDOT can be 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 800 parts by weight or less, 750 parts by weight or less, 700 parts by weight or less, 650 parts by weight or less, 600 parts by weight or less, 550 parts by weight or less, 500 parts by weight or less, 450 parts by weight or less, or 400 parts by weight or less, relative to 100 parts by weight of the polymer component.
[0114] In the synthesis of the conductive polymer PEDOT:PAA according to one embodiment of the present invention, by controlling the content ratio of PAA to EDOT within a range formed by appropriately selecting the above upper and lower limits, PAA:PEDOT suitable for the purpose of the present invention can be synthesized.
[0115] Furthermore, in the synthesis of the conductive polymer PEDOT:PAA according to one embodiment of the present invention, the weight-average molecular weight of the polymer component PAA can be 2000 g / mol or greater, 2500 g / mol or greater, 3000 g / mol or greater, 3500 g / mol or greater, 4000 g / mol or greater, 4500 g / mol or greater, or 5000 g / mol or greater, or 200,000 g / mol or less, 180,000 g / mol or less, 160,000 g / mol or less, 140,000 g / mol or less, 120,000 g / mol or less, or 100,000 g / mol or less. By using PAA having a weight-average molecular weight within the range defined by appropriately selecting the upper and lower limits above, PAA:PEDOT suitable for the purposes of the present invention can be synthesized. If the weight-average molecular weight of the polymer component serving as a template is outside the above range, the conductivity of the conductive polymer itself may be reduced, making it difficult to achieve the purposes of the present invention.
[0116] In the present invention, the weight average molecular weight (Mw) can be measured using gel permeation chromatography (GPC). In addition, the number average molecular weight (Mn) can also be measured using the GPC, and the polydispersity index (PDI) can be obtained by dividing the weight average molecular weight (Mw) measured above by the value (Mw / Mn) obtained by the number average molecular weight (Mn). Specifically, the method for measuring the weight average molecular weight and the polydispersity index can be found in the following <Methods for measuring physical properties>.
[0117] In an electrode according to one example of the present invention, the binder and the polymer component of the conductive polymer contained in the active material layer may each independently contain a resin that satisfies a specific formula. Specifically, the binder may contain a resin A that satisfies a specific formula, and the polymer component may contain a resin B that satisfies a specific formula. The binder may contain 55% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more of resin A relative to the total weight of the binder. In addition, the polymer component may contain 55% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more of resin B relative to the total weight of the polymer component. In an electrode according to one example of the present invention, by making the binder and the polymer component contained in the active material layer respectively contain resin A or resin B that satisfies the following specific formula, it is possible to ensure the characteristics of excellent conductivity and excellent capacity retention. In addition, the adhesive and polymer component may further contain resin A or resin B, respectively, and may further contain resin X that is different from resin A and resin B. Examples of the resin X can refer to the examples of the adhesive described above.
[0118] In addition, the resin A and the resin B may be the same type of resin, or may be different types of resins from each other.
[0119] In the electrode according to one example of the present invention, the binder included in the active material layer may include SP according to the following Formula 1: d 30 (MPa) 1 / 2 Below, 29 (MPa) 1 / 2 Below, 28 (MPa) 1 / 2 Below or 27 (MPa) 1 / 2 The following resin A (resin A). Wherein, the following formula 1 is related to the specific formula satisfied by the above resin A. The SP of the resin A according to the following formula 1 d The closer the lower limit of is to 0, the more favorable it is, so there is no particular limitation, but for example it can be 0 (MPa) 1 / 2 、0(MPa) 1 / 2 Above, greater than 0 (MPa) 1 / 2 , 1(MPa) 1 / 2 Above, 5(MPa) 1 / 2 Above or 10 (MPa) 1 / 2 According to the following formula 1, SP d The above upper and lower limits can be appropriately selected within the range formed. By making the adhesive contain SP according to the following formula 1 dResin A satisfying the above range can ensure excellent conductivity and excellent capacity retention.
[0120] In addition, in the electrode according to one example of the present invention, the polymer component may include SP according to the following Formula 1: d 30 (MPa) 1 / 2 Below, 29 (MPa) 1 / 2 Below, 28 (MPa) 1 / 2 Below or 27 (MPa) 1 / 2 The following resin B (resin B). Wherein, the following formula 1 is related to the specific formula satisfied by the above resin B. The SP of the resin B according to the following formula 1 d The closer the lower limit of is to 0, the more favorable it is, so there is no particular limitation, but for example it can be 0 (MPa) 1 / 2 、0(MPa) 1 / 2 Above, greater than 0 (MPa) 1 / 2 , 1(MPa) 1 / 2 Above, 5(MPa) 1 / 2 Above or 10 (MPa) 1 / 2 According to the following formula 1, SP d The above upper and lower limits can be appropriately selected within the range formed. By making the polymer component contain SP according to the following formula 1 d Resin B satisfying the above range can ensure excellent conductivity and excellent capacity retention.
[0121] Furthermore, in the electrode according to one example of the present invention, by combining the binder including the resin A and the polymer component including the resin B, characteristics of excellent conductivity and excellent capacity retention can be ensured.
[0122] [Formula 1]
[0123] SP d =SP W -SP P
[0124] In formula 1, SP W is the solubility parameter of water measured at 25°C, SP P is the solubility parameter of the resin A or the resin B measured at 25°C.
[0125] The term solubility parameter used in the present invention is to represent the value of the degree of mutual affinity between solute and solvent with numerical value, which can be used as an index of solubility. Polar solubility parameter, hydrogen bonding solubility parameter and dispersion solubility parameter are usually expressed as the value according to specific formula by the solubility parameter. The definition of the solubility parameter can be found in Barton, AFM (1991). Handbook of Solubility Parameters and Other Cohesion Parameters, 2nd edition. CRC Press (non-patent literature 1). In addition, the solubility parameter in the present invention can use known value. When there is no known value, it can be measured according to the method mainly known in the art. When mixed with two or more substances, the solubility parameter value of each substance can be used as the solubility parameter of the present invention based on the mean value of molar composition ratio (high performance liquid chromatography etc. can be used to calculate). For known solubility parameters of specific substances, see J. Brandrup, EH Immergut, and EA Grulke, des. Polymer Handbook, 4 th ed., Wiley-Interscience, New York, 1999. (Non-patent document 2), and for substances not shown in the non-patent document 2, see Yanlong Luo et al., 2017, J. Phys. Chem. C 2017, 121, 10163-10173 (Non-patent document 3).
[0126] According to one example, it is known that water has a viscosity of about 47.9 (MPa) at 25°C. 1 / 2 In addition, it is known that polyvinyl alcohol (PVA) has a solubility parameter of about 26 (MPa) at 25°C. 1 / 2 In addition, it is known that polyacrylic acid (PAA) has a solubility parameter of about 21 (MPa) at 25°C. 1 / 2 In addition, it is known that styrene-butadiene rubber (SBR) has a solubility parameter of about 17 (MPa) at 25°C. 1 / 2 That is, in order to make the SP of the resin A and the resin B according to the formula 1 dThe range defined above is satisfied, and styrene-butadiene rubber may preferably not be used. In addition, for example, resin A and resin B may each independently contain one or more selected from polyacrylic acid and polyvinyl alcohol. The types of resin A and resin B may be selected as long as they satisfy the SP according to the above formula 1. d The scope may be defined as such, and the invention is not necessarily limited to the above examples.
[0127] In the electrode according to one example of the present invention, the solubility parameter (SP) of the resin A measured at 25°C is P1 ) and resin B measured at 25 ° C solubility parameter (SP P2 ) ratio (SP P1 / SP P2 ) may be 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1 or less, 1.2 or less, 1.15 or less, 1.1 or less, or 1.05 or less. P1 / SP P2 ) can be included in the range formed by appropriately selecting the above upper and lower limits. When the ratio (SP P1 / SP P2 ) satisfies the above range, it is possible to ensure the characteristics of excellent conductivity and excellent capacity retention rate.
[0128] In the electrode according to one example of the present invention, the binder included in the active material layer may include a weight average molecular weight (M W1 ) is 2000 g / mol or more, 2500 g / mol or more, 3000 g / mol or more, 3500 g / mol or more, 4000 g / mol or more, 4500 g / mol or more or 5000 g / mol or less, or 200000 g / mol or less, 180000 g / mol or less, 160000 g / mol or less, 140000 g / mol or less, 120000 g / mol or less or 100000 g / mol or less. The weight average molecular weight of the resin A may be within the range formed by appropriately selecting the above upper and lower limits. By making the binder contain a resin A having a weight average molecular weight (M) within the above range, W1 ) of resin A, which can ensure the characteristics of excellent conductivity and excellent capacity retention.
[0129] In the electrode according to one embodiment of the present invention, the polymer component may include a weight average molecular weight (M W2) is 2000 g / mol or more, 2500 g / mol or more, 3000 g / mol or more, 3500 g / mol or more, 4000 g / mol or more, 4500 g / mol or more or 5000 g / mol or more, or 200000 g / mol or less, 180000 g / mol or less, 160000 g / mol or less, 140000 g / mol or less, 120000 g / mol or less or 100000 g / mol or less. The weight average molecular weight of the resin B may be within the range formed by appropriately selecting the above upper and lower limits. By making the polymer component contain a resin B having a weight average molecular weight (M) within the above range, W2 ) of resin B, which can ensure the characteristics of excellent conductivity and excellent capacity retention.
[0130] In the electrode according to one example of the present invention, in terms of achieving the purpose of the present invention, more preferably, the binder included in the active material layer may include a weight average molecular weight (M W1 ) Resin A in the range of 10,000 g / mol to 100,000 g / mol, 20,000 g / mol to 90,000 g / mol, or 30,000 g / mol to 70,000 g / mol.
[0131] In the electrode according to one embodiment of the present invention, the weight average molecular weight (M W1 ) and the weight average molecular weight of resin B (M W2 ) ratio (M W1 / M W2 ) can be 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, or 0.3 or less, 20 or less, 18 or less, 16 or less, or 14 or less. The ratio of the weight average molecular weight of the resin A to the weight average molecular weight of the resin B (M W1 / M W2 ) can be within the range formed by appropriately selecting the upper and lower limits. By making the ratio of the weight average molecular weight of the resin A to the weight average molecular weight of the resin B (M W1 / M W2 ) satisfies the above range, and can ensure the characteristics of excellent conductivity and excellent capacity retention rate.
[0132] In the electrode according to one example of the present invention, resin A and resin B may each independently have a glass transition temperature (Tg) of 50° C. or higher, 55° C. or higher, 60° C. or higher, 65° C. or higher, 70° C. or higher, 75° C. or higher, 80° C. or higher, 85° C. or higher, or 90° C. or higher. The upper limit of the glass transition temperature of resin A and resin B is not particularly limited, but may be 300° C. or lower, 250° C. or lower, 200° C. or lower, or 150° C. or lower.
[0133] In the electrode according to one example of the present invention, the binder included in the active material layer may include a glass transition temperature (T g1 ) is 50°C or higher, 55°C or higher, 60°C or higher, 65°C or higher, 70°C or higher, 75°C or higher, 80°C or higher, 85°C or higher, or 90°C or higher. That is, the glass transition temperature of the resin A may be 50°C or higher, 55°C or higher, 60°C or higher, 65°C or higher, 70°C or higher, 75°C or higher, 80°C or higher, 85°C or higher, or 90°C or higher. The upper limit of the glass transition temperature of the resin A is not particularly limited, but may be 300°C or lower, 250°C or lower, 200°C or lower, or 150°C or lower.
[0134] In addition, in the electrode according to one example of the present invention, the polymer component may include a glass transition temperature (T g2 ) is 50°C or higher, 55°C or higher, 60°C or higher, 65°C or higher, 70°C or higher, 75°C or higher, 80°C or higher, 85°C or higher, or 90°C or higher. That is, the glass transition temperature of the resin B may be 50°C or higher, 55°C or higher, 60°C or higher, 65°C or higher, 70°C or higher, 75°C or higher, 80°C or higher, 85°C or higher, or 90°C or higher. The upper limit of the glass transition temperature of the resin B is not particularly limited, but may be 300°C or lower, 250°C or lower, 200°C or lower, or 150°C or lower.
[0135] The term glass transition temperature used in the present invention may refer to a value measured using a differential scanning calorimeter (DSC) according to ISO 1135762. Specifically, the method of measuring the glass transition temperature may refer to the following <Measurement Methods of Physical Properties>.
[0136] In the electrode according to one embodiment of the present invention, the glass transition temperature (T g1 ) and the glass transition temperature of resin B (T g2 ) ratio (T g1 / T g2 ) may be 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1 or less, 1.2 or less, 1.15 or less, 1.1 or less, or 1.05 or less. g1 / T g2 ) may be included in the range formed when the above upper and lower limits are appropriately selected. When the ratio (T g1 / T g2 ) satisfies the above range, it is possible to ensure the characteristics of excellent conductivity and excellent capacity retention rate.
[0137] In the electrode according to one example of the present invention, the active material layer may include a binder (W B ) and conductive polymers (W CP In the active material layer, the weight of the binder (W B ) and the weight of the conductive polymer (W CP ) ratio (W B / W CP ) can be controlled to be greater than 1, greater than 1.5, greater than 2, greater than 2.5, greater than 3, greater than 3.5 or greater than 4, or less than 100, less than 90, less than 80, less than 70, less than 60, less than 50 or less than 40. In addition, the weight ratio (W B / W CP ) may be included in the range formed when the above upper limit and lower limit are appropriately selected. When the weight ratio (W B / W CP ) satisfies the above range, it is possible to ensure the characteristics of excellent conductivity and excellent capacity retention rate.
[0138] In an electrode according to an example of the present invention, the conductivity of the conductive polymer measured by a four-point probe method at 25°C may be 2×10 -3 S / cm or more, 2.5×10 -3 S / cm or more, 3×10 -3 S / cm or more, 3.5×10 -3 S / cm or more, 4×10 -3 S / cm or more, 4.5×10 -3 S / cm or more, 5×10 -3 S / cm or above or 5.5×10 -3 The higher the upper limit of the electrical conductivity, the more advantageous it is, and therefore there is no particular limitation.
[0139] The term conductivity used in the present invention may refer to a value measured by a four-point probe method. Specifically, the method for measuring conductivity using the four-point probe method can be referred to in the following <Measurement Method of Physical Properties>.
[0140] In the electrode according to one embodiment of the present invention, the active material layer may further contain a conductive material as needed. By making the active material layer further contain a conductive material, the conductivity can be improved and the density of the active material layer itself can be enhanced.
[0141] There are no particular limitations on the conductive material, as long as it does not cause chemical changes in the battery cell and exhibits conductivity. Examples of the conductive material include graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes (CNTs); metal powders, such as fluorocarbon powder, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials, such as polyphenylene derivatives.
[0142] In an electrode according to an example of the present invention, the active material layer may include carbon nanotubes as a conductive material. By making the active material layer include carbon nanotubes as a conductive material, better conductivity and excellent battery cell characteristics can be ensured. The carbon nanotubes can be divided into single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs) or multi-walled carbon nanotubes (MWCNTs) according to the number of carbon walls.
[0143] In an electrode according to one example of the present invention, the average diameter of the carbon nanotubes may be in the range of 0.5 nm to 100 nm, in the range of 1 nm to 80 nm, in the range of 1 nm to 60 nm, in the range of 1 nm to 40 nm, in the range of 1 nm to 20 nm, or in the range of 1 nm to 10 nm. Furthermore, the carbon nanotubes may have different average diameters depending on their type. For example, SWCNTs may have an average diameter in the range of 0.5 nm to 10 nm, in the range of 0.5 nm to 8 nm, or in the range of 1 nm to 5 nm. Furthermore, for example, MWCNTs may have an average diameter in the range of 1 nm to 60 nm, in the range of 1 nm to 50 nm, or in the range of 2 nm to 40 nm.
[0144] In an electrode according to an example of the present invention, the aspect ratio of the carbon nanotubes may be 100 or more, 110 or more, 120 or more, 130 or more, 140 or more, 150 or more, 160 or more, 170 or more, 180 or more, 190 or more, or 200 or more, or 10,000 or less, 9,000 or less, 8,000 or less, 7,000 or less, 6,000 or less, 5,000 or less, 4,000 or less, 3,000 or less, 2,000 or less, or 1,000 or less. In addition, the aspect ratio may be within a range formed by appropriately selecting the upper and lower limits. In addition, the carbon nanotubes may have different average diameters depending on their type. For example, SWCNTs can have an aspect ratio of 300 or more, 350 or more, 400 or more, 450 or more, 500 or more, 550 or more, or 600 or more, or 10,000 or less, 9,000 or less, 8,000 or less, 7,000 or less, 6,000 or less, 5,000 or less, 4,000 or less, 3,000 or less, 2,000 or less, or 1,000 or less. Also, for example, MWCNTs can have an aspect ratio of 100 or more, 110 or more, 120 or more, 130 or more, 140 or more, 150 or more, 160 or more, 170 or more, 180 or more, 190 or more, or 200 or more, or 1,000 or less, 900 or less, 800 or less, 700 or less, 600 or less, 500 or less, 400 or less, or 300 or less.
[0145] In an electrode according to one embodiment of the present invention, even if the active material layer contains a small amount of conductive material, a combination of a binder and a conductive polymer can be used to construct an economical production system, while achieving excellent conductivity and excellent capacity retention. Specifically, even when the amount of the somewhat expensive conductive material used in the active material layer is reduced by using an appropriate combination of a binder and a conductive polymer, a capacity retention rate similar to or better than that achieved when the conductive material is not reduced can be maintained.
[0146] In an electrode according to an example of the present invention, the active material layer may contain less than 0.2% by weight, less than 0.19% by weight, less than 0.18% by weight, less than 0.17% by weight, less than 0.16% by weight, less than 0.15% by weight, less than 0.14% by weight, less than 0.13% by weight, less than 0.12% by weight, less than 0.11% by weight or less than 0.1% by weight of a conductive material relative to the total weight of the active material layer. The active material layer containing a small amount of conductive material may refer to a conductive material containing less than the above upper limit. The lower limit of the content of the conductive material is not particularly limited, but the content of the conductive material may be more than 0.001% by weight, more than 0.005% by weight, more than 0.01% by weight, more than 0.02% by weight, more than 0.03% by weight, more than 0.04% by weight, more than 0.05% by weight, more than 0.06% by weight, more than 0.07% by weight, more than 0.08% by weight or more than 0.09% by weight relative to the total weight of the active material layer.
[0147] In the electrode according to one example of the present invention, an economical production system can be constructed by combining the contents of the conductive polymer and the conductive material in the active material layer, and excellent conductivity and excellent capacity retention can be achieved.
[0148] In an electrode according to an example of the present invention, the active material layer may contain more than 1 part by weight, more than 5 parts by weight, more than 10 parts by weight, more than 15 parts by weight, or more than 20 parts by weight, or less than 500 parts by weight, less than 450 parts by weight, less than 400 parts by weight, less than 350 parts by weight, less than 300 parts by weight, less than 250 parts by weight, or less than 200 parts by weight of a conductive material relative to 100 parts by weight of a conductive polymer. In addition, the content of the conductive material may be within a range formed by appropriately selecting the above upper and lower limits. As described above, by combining the contents of the conductive material and the conductive polymer in an appropriate ratio, an economical production system can be constructed, and excellent conductivity and excellent capacity retention can be achieved.
[0149] In an electrode according to an embodiment of the present invention, the active material layer may further contain a thickener, a reinforcing material, a leveling agent, or an electrolyte additive, etc., as needed. The types of these agents are not particularly limited, as long as they are used in the art.
[0150] The manufacturing method of an electrode according to an embodiment of the present invention may include the step of forming an active material layer. The manufacturing method of the electrode can refer to the composition of the electrode mentioned above.
[0151] Furthermore, as described above, the active material layer may be formed from a slurry composition. The slurry composition forming the active material layer may include the composition included in the above-mentioned active material layer.
[0152] The slurry composition can further include a solvent as needed. The solvent can be appropriately set by considering the desired performance, etc., and the solvent can be an aqueous solvent such as water (pure water or ultrapure water, etc.), an organic solvent, or a mixed solvent such as two or more solvents. For example, the solvent can use N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, methyl propionate, alcohol or ethyl propionate or an aqueous solvent such as water, but considering drying temperature or environmental influences, most preferably water. The content of the solvent can be selected by considering the performance of the desired battery core 1, etc.
[0153] The slurry composition can use an appropriate amount of solvent by considering the composition and dispersibility included. For example, the slurry composition can include 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, 100 parts by weight or more, or 10,000 parts by weight or less, 5,000 parts by weight or less, 3,000 parts by weight or less, 2,000 parts by weight or less, 1,000 parts by weight or less, 500 parts by weight or less, 300 parts by weight or less, or 200 parts by weight or less of a solvent, or can include a solvent within the range formed by appropriately selecting the above upper and lower limits.
[0154] In addition, the slurry composition may include the above-mentioned various components. In addition, the slurry composition may be in a state in which the above-mentioned various components are appropriately dispersed. The slurry composition can be prepared by adding the above-mentioned various components according to an appropriate method and order and then using an appropriate mixing method. The mixing method is not particularly limited, and known methods can be used. Specifically, the mixing method can use a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, an ultrasonic disperser, a homogenizer, a planetary mixer or a Filmix mixer.
[0155] In addition, the step of forming the active material layer can be performed by coating the slurry composition on a release film and drying the coated slurry composition. The release film can be removed so that the formed active material layer is attached to a current collector to manufacture an electrode.
[0156] In addition, the step of forming the active material layer can be performed by applying the slurry composition on a current collector and drying it. An electrode can also be manufactured by this method.
[0157] In addition, the coating method is not particularly limited, and known methods can be used. Specifically, the coating method can use a blade coating method, a dip coating method, a reverse roller coating method, a forward roller coating method, a gravure coating method, an extrusion method or a brush coating method, etc. In view of the thickness after drying, the coating thickness of the slurry composition can be coated with an appropriate thickness, and according to the coating thickness, the above-mentioned known method can be appropriately selected to carry out. In addition, the calendering method can be carried out according to a known method by a calendering fixture, etc.
[0158] The appropriate thickness can be adjusted by the loading amount of the slurry composition. The slurry composition can be applied at an appropriate loading amount suitable for the purpose. The loading amount is not particularly limited, but for example, it can be 1 mg / cm 2 Above, 2mg / cm 2 Above, 3mg / cm 2 Above, 4mg / cm 2 Above, 5mg / cm 2 Above, 6mg / cm 2 Above, 7mg / cm 2 Above or 8mg / cm 2 Above, or can be 50mg / cm 2 Below, 45mg / cm 2 Below, 40mg / cm 2 Below, 35mg / cm 2 Below, 30mg / cm 2 Below, 25mg / cm 2 Below, 20mg / cm 2 Below or 10mg / cm 2 Below, or within a range formed by appropriately selecting the above upper and lower limits.
[0159] In addition, the applied slurry composition can be dried at an appropriate temperature and time. The drying can be performed in an oven, and the oven temperature can be set to 50° C. or higher, 60° C. or higher, 70° C. or higher, 80° C. or higher, 90° C. or higher, or 100° C. or higher. In addition, the drying time can be performed within an appropriate range considering the drying temperature.
[0160] The basic unit that performs the charge and discharge functions may be referred to as a battery cell. Figure 1 Schematic diagram showing an exemplary structure of a battery cell 1 according to an example of the present invention. Figure 1 The battery cell 1 has a structure including a positive electrode 1a and a negative electrode 1b, with a separator 1c interposed between the positive electrode 1a and the negative electrode 1b. Furthermore, in the battery cell 1, the structure including the positive electrode 1a, the negative electrode 1b, and the separator 1c is referred to as an electrode assembly. The battery cell 1 has a structure including an exterior material 1e that can accommodate the electrode assembly, with an electrolyte 1d filled in a space sealed by the exterior material 1e.
[0161] A battery cell 1 according to an embodiment of the present invention may include a positive electrode 1a, a negative electrode 1b, and a separator 1c interposed between the positive and negative electrodes. The negative electrode 1b may be an electrode according to an embodiment of the present invention. That is, an electrode according to an embodiment of the present invention may be more preferably used as the negative electrode 1b of the battery cell 1.
[0162] In a battery cell 1 according to an embodiment of the present invention, the positive electrode 1a refers to a reduction electrode where an electron transport material receives electrons when the battery cell 1 is discharged, and the negative electrode 1b refers to an oxidation electrode where an electron transport material transports electrons when the battery cell 1 is discharged.
[0163] In the battery cell 1 according to one example of the present invention, in the following formula 2, when n is 100, L R It may be 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, 88% or more, 89% or more, 90% or more, 91% or more, 92% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, or 98% or more. In addition, in the battery cell 1, in the following formula 2, when n is 200, L R It may be 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, 65% or more, 66% or more, 67% or more, 68% or more, 69% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 79% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, or 85% or more.
[0164] [Formula 2]
[0165] L R =L2 / L1×100(%)
[0166] In Equation 2, L1 is the discharge capacity of the first cycle at 25°C, and L2 is the discharge capacity of the nth cycle at 25°C, where one cycle is defined as charging to 4.2 V at 0.5C and CC-CV charging mode at 25°C, then discharging to 2.7 V at 0.5C after 0.05C.
[0167] In the battery cell 1 according to one embodiment of the present invention, it can be seen that by making L according to the formula 2 R The above values are satisfied during each cycle to ensure conductivity and excellent capacity retention. R The measurement can be performed based on the case where an electrode according to an example of the present invention is used as the negative electrode and lithium metal is used as the counter electrode. More specifically, after a battery cell 1 is manufactured according to the following embodiment, the measurement can be performed based on the manufactured battery cell 1.
[0168] In the battery cell 1 according to an embodiment of the present invention, as described above, the electrode according to an embodiment of the present invention can be used as the negative electrode 1b. The active material layer of the negative electrode 1b can contain SWCNT as a conductive material. In the formula 2, when n is 100, L R The active material layer of the negative electrode 1b may contain SWCNT as a conductive material. In Formula 2, when n is 200, L RThe SWCNT content may be 78% or more, 78.1% or more, 78.2% or more, 78.3% or more, 78.4% or more, 78.5% or more, 78.6% or more, 78.7% or more, 78.8% or more, 78.9% or more, 79% or more, 79.1% or more, 79.2% or more, 79.3% or more, 79.4% or more, 79.5% or more, 79.6% or more, 79.7% or more, 79.8% or more, 79.9% or more, or 80% or more. The SWCNT content may be 0.2% or less, 0.19% or less, 0.18% or less, 0.17% or less, 0.16% or less, 0.15% or less, 0.14% or less, 0.13% or less, 0.12% or less, 0.11% or less, or 0.1% or less, relative to the total weight of the active material layer. In the battery cell 1 according to one example of the present invention, even if a smaller amount of conductive material is included, an economical production system can be constructed by applying an electrode made of a combination of a binder and a conductive polymer as a negative electrode, and excellent conductivity and excellent capacity retention can be ensured.
[0169] In the battery cell 1 according to an embodiment of the present invention, as described above, the electrode according to an embodiment of the present invention can be used as the negative electrode 1b. The active material layer of the negative electrode 1b can use MWCNT as a conductive material. In the formula 2, when n is 100, L R It can be 85% or more, 85.2% or more, 85.4% or more, 85.6% or more, 85.8% or more, 86% or more, 86.2% or more, 86.4% or more, 84.6% or more, 84.8% or more, 85% or more, 85.2% or more, 85.4% or more, 85.6% or more, 85.8% or more, 86% or more, or 86.2% or more. In addition, the active material layer of the negative electrode 1b can use MWCNT as a conductive material. In the formula 2, when n is 200, L RThe content of the MWCNTs may be 65% or more, 65.1% or more, 65.2% or more, 65.3% or more, 65.4% or more, 65.5% or more, 65.6% or more, 65.7% or more, 65.8% or more, 65.9% or more, 66% or more, 66.1% or more, 66.2% or more, 66.3% or more, 66.4% or more, 66.5% or more, or 66.6% or more. The content of the MWCNTs may be 0.2% or less, 0.19% or less, 0.18% or less, 0.17% or less, 0.16% or less, 0.15% or less, 0.14% or less, 0.13% or less, 0.12% or less, 0.11% or less, or 0.1% or less, relative to the total weight of the active material layer. In the battery cell 1 according to one example of the present invention, even if a smaller amount of conductive material is included, an economical production system can be constructed by applying an electrode made of a combination of a binder and a conductive polymer as a negative electrode, and excellent conductivity and excellent capacity retention can be ensured.
[0170] In a battery cell 1 according to an embodiment of the present invention, the positive electrode 1a can be manufactured by coating a positive electrode slurry composition on a positive electrode current collector and then drying it to form a positive electrode active material layer. Rolling can be performed after drying as needed. The coating, drying, and rolling steps in the method for manufacturing the positive electrode 1a can be found in the method for manufacturing an electrode according to an embodiment of the present invention.
[0171] The positive electrode current collector is not particularly limited in type, size, or shape as long as it does not cause chemical changes in the battery cell 1 and has conductivity. The positive electrode current collector may be made of, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver.
[0172] In addition, the positive electrode current collector may have an appropriate thickness as needed. Although not particularly limited, the positive electrode current collector may have a thickness in the range of 1 μm to 500 μm, or may have a thickness in the range of 1 μm to 300 μm, or may have a thickness in the range of 1 μm to 100 μm, or may have a thickness in the range of 1 μm to 50 μm.
[0173] In addition, the positive electrode current collector may have fine concavo-convex surfaces to further enhance the adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be in the form of one or more selected from a film, sheet, foil, mesh, porous body, foam, and non-woven fabric.
[0174] The positive electrode active material layer may include a positive electrode active material. The positive electrode active material is not particularly limited, but for example, it can be exemplified by: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or compounds substituted with one or more transition metals; lithium iron oxides such as LiFe3O4; 1+c1 Mn 2-c1 Lithium manganese oxides such as LiMnO4 (0≤c1≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 or Cu2V2O7; 1-c2 M c2 Ni-site lithium nickel oxide represented by O2 (wherein M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); 2-c3 M c3 Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from Fe, Co, Ni, Cu and Zn); lithium nickel cobalt manganese (NCM) composite oxides, lithium nickel cobalt manganese aluminum (NCMA) composite oxides and LiMn2O4 in which part of the Li in the chemical formula is substituted by alkaline earth metal ions, etc.
[0175] The positive electrode active material layer may include a binder. The specific type of the binder is not particularly limited, and the binder can be a substance that improves the adhesion between the positive electrode active materials and the adhesion between the positive electrode active material layer and the positive electrode current collector.
[0176] The binder of the positive electrode active material layer can be, for example, one or more selected from polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), polyethylene oxide, carboxymethyl cellulose (CMC), cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer (poly(ethylene-co-vinyl acetate) copolymer) and polyarylate.
[0177] The positive electrode active material layer may further include a conductive material. The conductive material is not particularly limited as long as it does not cause chemical changes in the battery cell and has conductivity. For example, the conductive material can use graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes (CNTs); metal powders such as fluorocarbon powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc.
[0178] The positive electrode slurry composition forming the positive electrode active material layer may include the above-mentioned positive electrode active material and a binder, and may further include a conductive material as needed. In addition, the positive electrode slurry composition may further include a solvent. The solvent can be appropriately set by considering the desired performance, etc., and the solvent may be an aqueous solvent such as water (pure water or ultrapure water, etc.), an organic solvent, or a mixed solvent of two or more. For example, the solvent may be an organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, a propylene carbonate derivative, a tetrahydrofuran derivative, methyl propionate, an alcohol, or ethyl propionate, or an aqueous solvent such as water. The content of the solvent may be selected in consideration of the desired performance of the battery cell 1, etc.
[0179] The positive electrode slurry composition forming the positive electrode active material layer can appropriately adjust the content ratio of the active material to the binder and the content ratio of the conductive material to the solvent to achieve the purpose. These content ratios can be applied to known content ratios.
[0180] The positive electrode 1a may contain lithium metal as needed for test evaluation.
[0181] In addition, the separator 1c refers to a film that prevents the short circuit between the positive electrode and the negative electrode and allows the electron transport material to pass through. As long as the separator is a separator commonly used in the present technical field, it can be used without particular restriction. In particular, the separator preferably has low resistance to the ion migration of the electrolyte and has excellent wettability (wettability, wettability) of the electrolyte. Specifically, the separator can use a porous polymer film, for example, a porous polymer film made of polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a stacked structure of more than two layers thereof. In addition, the separator can use conventional porous non-woven fabrics, for example, non-woven fabrics made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc. In addition, in order to ensure heat resistance or mechanical strength, a separator comprising a coating of a ceramic component or a polymer substance can be used, and can optionally be used with a single-layer structure or a multilayer structure.
[0182] In addition, the electrolyte 1d refers to a medium that causes the migration of electron transport substances to facilitate the electrochemical reaction of the positive electrode 1a and the negative electrode 1b. The electrolyte can use commonly used organic liquid electrolytes, inorganic liquid electrolytes, gel-type polymer electrolytes, molten inorganic electrolytes, etc., but is not limited thereto. In addition, Figure 1 1d shows a liquid electrolyte, but as mentioned above, a solid electrolyte such as a gel polymer electrolyte can also be used. Batteries using solid electrolytes are generally called solid-state batteries or all-solid-state batteries. In the case of a liquid electrolyte, it generally contains an organic solvent and a lithium salt.
[0183] The organic solvent can be used without special restrictions as long as it can play the role of a medium for the migration of ions participating in the electrochemical reaction of the battery cell. Specifically, the organic solvent can use ester-based solvents such as methylacetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (EPC). carbonate, PC) and other carbonate-based solvents; alcohol-based solvents such as ethanol and isopropyl alcohol; nitriles such as R-CN (R is a linear, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, and may contain a double bond aromatic ring or an ether bond) and amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane (sulfolane) and the like. Among them, the organic solvent is preferably a carbonate-based solvent, and more preferably a mixture of a cyclic carbonate (for example, ethylene carbonate or propylene carbonate, etc.) having high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery cell and a low-viscosity chain carbonate-based compound (for example, ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, by mixing the cyclic carbonate and the chain carbonate in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be exhibited.
[0184] The lithium salt can be used without particular limitation as long as it is a compound that can provide lithium ions. Specifically, the lithium salt can use LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. The concentration of the lithium salt is preferably used in the range of 0.1-2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and thus can exhibit excellent electrolyte performance, and lithium ions can be effectively transferred.
[0185] In addition to the components of the electrolyte, the electrolyte may further contain one or more additives for the purpose of improving the life characteristics of the battery, suppressing the reduction of the battery capacity, and increasing the discharge capacity of the battery, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glycol dimethyl ether (n-glyme), hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, or aluminum chloride. In this case, the content of the additives may be 0.1-5% by weight relative to the total weight of the electrolyte.
[0186] In the above, the battery is classified into various categories according to the type of electron transport material. For example, when the electron transport material is lithium (Li, including ions), the battery is called a lithium-ion battery.
[0187] In addition, the outer packaging material 1e can protect the positive electrode 1a, negative electrode 1b and separator 1c from external impact and prevent the electrolyte 1d from leaking to the outside. Depending on the shape of the outer packaging material 1e, the battery cell 1 can be classified as a prismatic, cylindrical or pouch type.
[0188] A battery module 2 according to one embodiment of the present invention may include one or more battery cells 1. The battery cells 1 may be the battery cells 1 according to one embodiment of the present invention. The battery cells 1 are assembled in a predetermined number and enclosed in a housing to protect them from external impacts, heat, vibration, and the like. Patent Document 1 discloses an example of a battery module. Figure 2 : is a schematic diagram showing an exemplary structure of a battery module 2 according to an example of the present invention. Figure 2The battery module 2 may have a structure including a battery cell unit 2a, an upper shell 2b-2, a lower shell 2b-1, a bus bar 2c, and an inner cover 2d-1 and an outer cover 2d-2.
[0189] The battery cell unit 2a may include more than one battery cell 1. In the case of multiple battery cells 1, the battery cells 1 may be connected in series and / or in parallel. The battery cell unit 2a may be built into the space formed by the lower shell 2b-1 and the upper shell 2b-2. However, the method of building the battery cell unit 2a is not limited to Figure 2 .
[0190] In addition, the battery cell 1 includes a positive tab extending from the positive electrode and a negative tab extending from the negative electrode. The battery cell unit 2a has a structure in which the positive and negative tabs protrude in accordance with the number of battery cells 1 included. The positive and negative tabs can be electrically coupled to a bus bar 2c having slits. Electrical coupling is achieved by inserting the positive and negative tabs, respectively, into the slits of the bus bar 2c. Furthermore, the battery module 2 includes an inner cover 2d-1 and an outer cover 2d-2 to cover the bus bar 2c and the battery cell unit 2a.
[0191] A battery pack 3 according to an embodiment of the present invention (see Figure 3 ) may include one or more battery cells 1 or one or more battery modules 2. The battery cell 1 may be a battery cell 1 according to an example of the present invention. In addition, the battery module 2 may be a battery module 2 according to an example of the present invention. The battery pack is a structure provided with various control devices and protection systems such as a battery management system (BMS) and a cooling device. Patent document 2 discloses an example of a battery pack. However, in recent years, there is a case where the battery pack 3 is directly composed of battery cells 1 instead of battery modules 2. In this case, it is called a cell-to-pack.
[0192] Figure 3 : is a schematic diagram showing an exemplary structure of a battery pack 3 according to an example of the present invention. Figure 3 The battery pack 3 is provided with one or more battery modules 2 and electronic components 3e, such as various control devices such as a BMS, in a storage space 3c formed inside the battery pack housing 3a.
[0193] The battery pack 3 may be provided with a cross beam 3d and a partition 3c to ensure the structural rigidity of the battery pack housing 3a. The cross beam 3d spans across the entire bottom 3a-1 and protrudes from the bottom 3a-1 of the battery pack housing 3a to connect the oppositely arranged side wall portions 3a-2 of the battery pack housing 3a. The partition 3c protrudes from the bottom 3a-1 of the battery pack housing 3a in a form connecting the cross beam 3d and the side wall portion 3a-2.
[0194] The electrical device according to an example of the present invention may include one or more selected from one or more battery cells 1, one or more battery modules 2, and one or more battery packs 3. The battery cell 1, the battery module 2, and the battery pack 3 may be the battery cell, the battery module, and the battery pack according to an example of the present invention. The electrical device refers to a device that operates by the electric power generated in the battery cell 1, etc., and may be, for example, a mobile phone, a household appliance, an electric vehicle, a hybrid vehicle, or an energy storage device (Energy Storage System, ESS). Detailed Description of the Invention
[0195] <Method for Measuring Physical Properties>
[0196] The following physical properties are measured as follows.
[0197] 1. Weight-average molecular weight and polydispersity index
[0198] The weight-average molecular weight (Mw) is measured using gel permeation chromatography (GPC). Specifically, the weight-average molecular weight (Mw) can be measured by the following method: The sample to be analyzed is placed in a 5 mL vial, diluted with a tetrahydrofuran (THF) solvent to a concentration of about 1 mg / mL, and then the calibration standard sample and the analysis sample are filtered through a syringe filter (pore size: 0.45 μm), and the weight-average molecular weight (Mw) is measured. The analysis program uses ChemStation of Agilent Technologies, and the weight-average molecular weight (Mw) can be obtained by comparing the elution time of the sample with the calibration curve. The number-average molecular weight (Mn) can also be measured by the same method. The value (M W ) obtained by dividing the weight-average molecular weight (Mw) measured as above by the number-average molecular weight (Mn) (M W / Mn) is the polydispersity index (PDI).
[0199] <GPC Measurement Conditions>
[0200] Device: Agilent Technologies 1200 series
[0201] Column: TL Mix. A&B from Agilent Technologies
[0202] Solvent: Tetrahydrofuran (THF)
[0203] Column temperature: 35°C
[0204] Sample concentration: 1 mg / mL, inject 200 μl
[0205] Standard sample: Polystyrene (MP: 3900000, 723000, 316500, 52200, 31400, 7200, 3940, 485)
[0206] 203
[0207] 2. Average particle size
[0208] The average particle size is the D50 particle size of the measured object, which is measured using a Malvern MASTERSIZER 3000 device according to ISO-13320. Distilled water is used as the solvent for measurement. Since the measured object is dispersed in the solvent, the incident laser light is scattered. The intensity and directionality of the scattered laser light vary depending on the size of the measured object. By analyzing this using Mie theory, the D50 particle size can be obtained. Through this analysis, a distribution diagram can be obtained by converting it into the diameter of a sphere with the same volume as the dispersed measured object. From this, the median D50 value of the distribution diagram can be obtained, thereby evaluating the particle size.
[0209] 3. Glass transition temperature
[0210] The glass transition temperature is measured using a conventional differential scanning calorimeter (DSC) apparatus. A DSC-STAR3 apparatus (Mettler Toledo) is used. Approximately 10 mg of the sample is sealed in a dedicated crucible (pan), and the temperature is raised at 10°C / minute. The glass transition temperature is measured by observing the amount of heat absorbed and released depending on the temperature.
[0211] 4. Conductivity
[0212] The conductivity is measured by a four-point probe method at 25°C. Specifically, four probes with a spacing of 1 mm and arranged in a row are attached to the sample and measured with an electrical measuring instrument (sourcemeter). The sample is prepared by the following method: the measurement object for measuring the conductivity is dispersed or dissolved in a solvent, and coated on a release film made of polyethylene terephthalate (PET) so that the thickness after drying is 200 nm, and then fully dried at a temperature of more than 100°C to form a sheet, and the formed sheet is separated from the release film to prepare the sample. In the case of a conductive polymer, water is used as a solvent and is coated and dried to form a sheet, and the formed sheet is used as the sample.
[0213] 5. Resistance of the active material layer
[0214] The resistance of the active material layer was measured as powder resistance using a four-point probe method. Specifically, the sample used particles prepared by vacuum drying the active material slurry at 100°C for 30 minutes and then pulverizing it to prepare a powder. The particles were then prepared using Mitsubishi Chem Analytic's Loresta GP equipment at 25°C, 50% relative humidity, and a load of 9.8 MPa.
[0215] 6. Capacity retention rate
[0216] The capacity retention rate is calculated by the following formula 2: R To obtain.
[0217] [Formula 2]
[0218] L R =L2 / L1×100(%)
[0219] In Equation 2, L1 is the discharge capacity of the first cycle at 25°C, and L2 is the discharge capacity of the nth cycle at 25°C, where one cycle is defined as charging to 4.2 V at 0.5C and CC-CV charging mode at 25°C, then discharging to 2.7 V at 0.5C after 0.05C.
[0220] Preparation Example 1
[0221] 3,4-ethylenedioxythiophene (EDOT) and polyacrylic acid (PAA) as monomers were mixed at a weight ratio of 5:5 (EDOT:PAA), and an appropriate amount of an oxidant such as ammonium persulfate (APS) was added, followed by mixing in water (solid content: 4.62%). The weight average molecular weight (M W ) is in the range of about 30,000 g / mol to 70,000 g / mol. It is known that the solubility parameter of the PAA measured at 25° C. is about 21 (MPa) 1 / 2 .
[0222] The mixture was then stirred at approximately 25°C for approximately 24 hours to induce the synthesis reaction of poly(3,4-ethylenedioxythiophene) (PEDOT). Simultaneously, PAA was also ionized. As PEDOT was synthesized, PEDOT electrically bonded to the ionized PAA, thereby synthesizing PEDOT:PAA. As the synthesis of PEDOT:PAA progressed, the reaction solution turned dark blue. The resulting solution was then dialysis bagged to remove impurities, placed in an ion exchange resin (a 1:1 (weight) mixture of MP62 and S100 from Lanxess) and stirred again to remove ionic impurities, thereby obtaining purified PEDOT:PAA as a conductive polymer. The PEDOT:PAA prepared according to Preparation Example 1 is represented by the following structural formula A. In the following structural formula A, n and m can be determined based on, for example, the weight ratio of EDOT to PAA and the weight-average molecular weight of the PAA.
[0223] [Structural Formula A]
[0224]
[0225] Preparation Example 2 to Preparation Example 10
[0226] Preparation Examples 2 through 10 are examples prepared by partially modifying the content ratios and weight-average molecular weights of Preparation Example 1. Table 1 below shows the content ratios and weight-average molecular weights of the compositions of each Preparation Example. In Preparation Examples 2 through 10, except for the details shown in Table 1, the conductive polymer represented by Structural Formula A, namely, purified PEDOT:PAA, was obtained by the same method as in Preparation Example 1. In Structural Formula A, n and m can be determined based on the weight ratio of EDOT to PAA and the weight-average molecular weight of PAA in each Preparation Example.
[0227] [Table 1]
[0228]
[0229] Evaluation results of conductivity of Preparation Examples 5 to 10
[0230] The electrical conductivity of Preparation Examples 5 to 10 prepared as described above is shown in the following Table 2. The electrical conductivity was measured by a four-point probe method at 25° C. according to the above-mentioned <Evaluation Method of Physical Properties>.
[0231] [Table 2]
[0232]
[0233] As shown in Table 2, when the weight-average molecular weight of PAA is outside the specified range, a conductive polymer having a desired level of conductivity cannot be formed. Furthermore, as shown in Table 2, when the weight-average molecular weight of PAA is within the specified range, a conductive polymer having an excellent level of conductivity can be formed.
[0234] Examples 1 to 10 and Comparative Examples 1 to 5
[0235] (1) Manufacturing of negative electrode
[0236] The active material slurry prepared according to Table 3 below was added at a concentration of 8-9 mg / cm 2 The active material slurry was coated on a copper foil having a thickness of about 8-10 μm. The copper foil coated with the active material slurry was vacuum dried at 100° C. for 30 minutes and then rolled to manufacture a negative electrode including an active material layer.
[0237] The active material slurry for manufacturing the negative electrode was prepared by mixing the active material slurry according to the weight ratio shown in Table 2 below and adding an appropriate amount of pure water (deionized water).
[0238] [Table 3]
[0239]
[0240] In Table 3, the active material (A) used was a mixture of a carbon active material (A1) having an average particle size of about 12 μm and a silicon active material (A2) having an average particle size of about 6 μm at a weight ratio of 9:1 (A1:A2). The carbon active material (A1) used was a mixture of artificial graphite (A11) and natural graphite (A12) at a weight ratio of 7:3 (A11:A12), and the silicon active material (A2) used was SiO x In addition, in Table 3, the binder (B) uses polyacrylic acid (PAA). The weight average molecular weight (M W) is about 30,000 g / mol to 70,000 g / mol. In addition, the glass transition temperature (Tg) of PAA used as the binder is about 100° C. In addition, it is known that the solubility parameter of PAA used as the binder measured at 25° C. is about 21 (MPa). 1 / 2 In Table 3, SWCNTs use single-walled carbon nanotubes having an average diameter of about 1-2 nm and an aspect ratio of about 1000 or greater. In Table 3, MWCNTs use multi-walled carbon nanotubes having an average diameter of about 3-40 nm and an aspect ratio of about 200 or greater.
[0241] (2) Manufacturing of battery cells
[0242] Each negative electrode manufactured as described above was used as a working electrode, a lithium metal sheet having a thickness of approximately 150 μm was used as a reference electrode, and a polyethylene separator (thickness: 20 μm, porosity: 40%) was placed between the negative electrode and the lithium metal sheet to manufacture an electrode assembly. The manufactured electrode assembly was placed in a battery container and injected with an electrolyte, and then a 2032 half-battery cell was manufactured according to a conventional manufacturing method.
[0243] The electrolyte used was an electrolyte in which LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) at a weight ratio of 3:2:5 (EC:PC:DEC) to a concentration of 1.3 M.
[0244] The resistance of the negative electrode active material layers (active material resistance) of Examples 4 to 9 and Comparative Examples 1 to 5 manufactured as described above is shown in Table 4. The resistance of the active material layer was measured according to the above-mentioned <Evaluation Method of Physical Properties>.
[0245] In addition, the capacity retention of the half-cells of Examples 1 to 9 and Comparative Examples 1 to 6 manufactured as described above is shown in Table 4 below. The capacity retention of the battery cells was measured according to the above-mentioned <Evaluation Method of Physical Properties>. In Table 4 below, the value of the capacity retention refers to the L according to the following [Formula 2] R value.
[0246] [Formula 2]
[0247] L R =L2 / L1×100(%)
[0248] In Equation 2, L1 is the discharge capacity of the first cycle at 25°C, and L2 is the discharge capacity of the nth cycle at 25°C, where one cycle is defined as charging to 4.2 V at 0.5C and CC-CV charging mode at 25°C, then discharging to 2.7 V at 0.5C after 0.05C.
[0249] [Table 4]
[0250]
[0251] In Table 4, when comparing Examples 4 and 5 with Comparative Example 1, it can be seen that the Examples using the conductive polymer exhibited a more excellent capacity retention rate. In addition, in Table 4, when comparing Examples 1 to 3, 6, 7, and 10 with Comparative Example 2, it can be seen that the Examples exhibited a more excellent capacity retention rate. That is, in the Examples, even if the same type (SWCNT) and amount (0.1 parts by weight) of conductive material as in the Comparative Example were applied, more excellent performance could be ensured by applying the conductive polymer. In addition, in Table 4, when comparing Examples 1 to 3, 6, 7, and 10 with Comparative Example 3, it can be seen that the Examples exhibited a more excellent or similar capacity retention rate than the Comparative Example. That is, it can be seen that in the Examples (0.1 parts by weight), more excellent or similar performance can be ensured compared to the Comparative Example (0.25 parts by weight) using a larger amount of the same type of conductive material (SWCNT).
[0252] Furthermore, when comparing Examples 8 and 9 with Comparative Example 4 in Table 4, it can be seen that the Examples exhibited superior capacity retention. That is, even when the same type (MWCNT) and amount (0.1 parts by weight) of conductive material as in the Comparative Example were used, superior performance was achieved by using a conductive polymer.
[0253] Furthermore, in Table 4, when comparing Examples 8 and 9 with Comparative Example 5, it can be seen that the Examples exhibited superior capacity retention. Specifically, it can be seen that the Examples (0.1 parts by weight) can achieve superior or similar performance compared to the Comparative Example (0.25 parts by weight) using a larger amount of the same type of conductive material (MWCNTs).
[0254] [Explanation of Reference Numerals]
[0255] 1: Battery cell
[0256] 2: Battery module
[0257] 3: Battery pack
Claims
1. An electrode comprising a current collector and an active material layer located on at least one side of the current collector, in, The active material layer comprises an active material, a binder and a conductive polymer, The conductive polymer comprises a conductive component and an ionized polymer component, The adhesive comprises SP according to the following formula 1 d 30 (MPa) 1 / 2 The following resin A, The polymer component comprises SP according to the following formula 1 d 30 (MPa) 1 / 2 The following resin B, [Formula 1] SP d =SP W -SP P In formula 1, SP W is the solubility parameter of water measured at 25°C, SP P is the solubility parameter of the resin A or the resin B measured at 25°C.
2. The electrode according to claim 1, wherein The solubility parameter SP of the resin A measured at 25°C is P1 The solubility parameter SP measured with the resin B at 25 °C P2 SP P1 / SP P2 In the range of 0.8 to 1.
2.
3. The electrode according to claim 1, wherein The weight average molecular weight M of the resin A W1 The weight average molecular weight M of the resin B W2 Ratio M W1 / M W2 In the range of 0.1 to 20.
4. The electrode according to claim 1, wherein The weight average molecular weight M of the resin B W2 In the range of 2000 g / mol to 200000 g / mol.
5. The electrode according to claim 1, wherein The resin A and the resin B each independently have a glass transition temperature Tg of 50° C. or higher.
6. The electrode according to claim 1, wherein The conductivity of the conductive polymer measured by the four-point probe method at 25°C is 2×10 -3 S / cm or more.
7. The electrode according to claim 1, wherein The conductive component and the ionized polymer component in the conductive polymer are electrically combined.
8. The electrode according to claim 1, wherein The conductive polymer includes 10 wt % or more of an ionized polymer component relative to the total weight of the conductive polymer.
9. The electrode according to claim 8, wherein The conductive polymer includes a conductive component in a range of 30 parts by weight to 800 parts by weight relative to 100 parts by weight of an ionized polymer component.
10. The electrode according to claim 1, wherein The weight W of the adhesive B The weight W of the conductive polymer CP The ratio W B / W CP On a scale of 1 to 100.
11. The electrode according to claim 1, wherein The content of the conductive polymer is 1 wt % or less relative to the total weight of the active material layer.
12. The electrode according to claim 1, wherein The content of the active material is in the range of 80 wt % to 99 wt % relative to the total weight of the active material layer.
13. The electrode according to claim 1, wherein The active material includes a carbon active material and a silicon active material.
14. The electrode according to claim 13, wherein The active material includes 80 to 99 wt % of a carbon active material relative to the total weight of the active material, and the active material includes 0.01 to 30 parts by weight of a silicon active material relative to 100 parts by weight of the carbon active material.
15. The electrode according to claim 13, wherein The average particle size D of the carbon active material in the active material C The average particle size D of the silicon active material Si Ratio D C / D Si In the range of 0.1 to 10.
16. The electrode according to claim 1, wherein The active material layer further includes a conductive material, and the content of the conductive material is 0.2 wt % or less relative to the total weight of the active material layer.
17. A battery cell comprising a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode. in, The negative electrode is the electrode according to claim 1, In the following formula 2, when n is 100, L R More than 80%, when n is 200, L R More than 55%, [Formula 2] L R =L2 / L1×100(%) In Equation 2, L1 is the discharge capacity of the first cycle at 25°C, and L2 is the discharge capacity of the nth cycle at 25°C, where one cycle is defined as charging to 4.2 V at 0.5C and CC-CV charging mode at 25°C, then discharging to 2.7 V at 0.5C after 0.05C.
18. A battery module comprising one or more battery cells. in, The battery cell is the battery cell according to claim 17.
19. A battery pack comprising one or more battery cells or one or more battery modules. in, The battery cell is the battery cell according to claim 17, and the battery module is the battery module according to claim 18.
20. An electrical device comprising one or more battery cells, one or more battery modules, and one or more battery packs. in, The battery cell is the battery cell according to claim 17, the battery module is the battery module according to claim 18, and the battery pack is the battery pack according to claim 19.
Citation Information
Patent Citations
Battery pack and manufacturing method thereof
KR1020220142853A
Battery module having excellent cooling efficient
KR1020220150693A